Technology of mushroom cultivation - Thuy, Quyen Ho Bao; Suzuki, Akira (Vietnam Journal of Science and Technology, 2019)
Mushroom cultivation has been developed by two ways, i. e., one based on cultivation by wood-log and another based on cultivation by non-wood-log. Non-wood-log cultivation would be categorized into two aspects. Mushroom cultivation under non-aseptic condition, i. e., one characterized by the processes of fermentation (composting) and casing, and another characterized by using sterilized media followed by cultivation process associated with strict control of environmental factors such as light, temperature, humidity, and CO2 concentration.